Alkali-Oxygen Impregnation Prior to Steam Pretreating Poplar Wood Chips Enhances Selective Lignin Modification and Removal while Maximizing Carbohydrate Recovery, Cellulose Accessibility, and Enzymatic Hydrolysis - Chu, Qiulu; Chandra, Richard P.; Kim, Chang-Soo; Saddler, Jack N. (American Chemical Society, 2017)
Poplar wood chips were impregnated with oxygen and sodium carbonate at relatively mild conditions (110 and 135 degrees C) prior to steam pretreatment (210 degrees C, 5 min) with the goal of selectively fractionating and modifying lignin while improving overall carbohydrate recovery and the ease of enzymatic hydrolysis of the cellulose. Using these pretreatment conditions more than 80% of the carbohydrate components (cellulose and hemicellulose) were retained in the water insoluble fraction, an 18% increase in hemicellulose recovery was achieved, while 58% of the original lignin could be extracted. Alkaline oxygen impregnated steam pretreatment also enriched the bulk acid group content of the substrate from 33 to 156 mmol/kg, consequently increasing both the water retention value of the substrate from 2.5 to 2.9 and cellulose accessibility as indicated by the increased adsorption of Direct Orange dye from 119 to 146 mg/g. The combination of lignin modification/removal enhanced substrate swelling and increased cellulose accessibility resulting in enzymatic hydrolysis yields of 86% of the cellulose and xylan after 48 h at an enzyme loading of 20 mg/g glucan and a solids loading of 10%. Impregnation with either oxygen or alkali alone, prior to steam pretreatment, was far less effective than impregnation with the alkali/oxygen combination. Alkali-oxygen steam pretreatment resulted in the retention of more carbohydrate in the water-insoluble fraction while increasing the ease of lignin extraction, enhanced cellulose accessibility, and better enzymatic hydrolysis of the cellulose component.